(untitled) (Texas Journal of Medical Science, 2024)
Breast cancer requires adequate diagnosis at the preoperative stage and a certain scheme of investigation of surgical and biopsy material. The prognosis and further tactics of treatment of patients depend on the result of histological examination with determination of receptor status (IHC-study) of breast cancer. Static data of breast cancer detection with the use of IHC-study on the basis of Tashkent City Dispensary for the period of 2020-2022 are indicated in the article.